Characterization of phenolics and antioxidant abilities of red navel orange "Cara Cara" harvested from five regions of China. Issue 1 (1st January 2018) - Lu, Qi; Lv, Siyi; Peng, Ying; Zhu, Chunhua; Pan, Siyi
ABSTRACT: Red-flesh navel orange "Cara Cara" is attractive for customers with its bright red color and has been widely planted in China. In this study, phenolic compounds in "Cara Cara" harvested from five different regions were identified and quantified by ultra high performance liquid chromatography (UPLC) coupled with Quadrupole-Time of Flight -Electrospray ionization-mass spectrometry (Q-TOF-ESI-MS n ). Their antioxidant abilities were evaluated by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and oxygen radical absorption capacity (ORAC) assays. Twenty phenolics were detected in crude extraction, with hesperidin (29.36–44.06%) as the dominant component, followed by narirutin (13.44–17.03%) and apigenin-6, 8-di-C-glucoside (8.28–12.38%). No free phenolic acid was found in crude extracts and three free phenolic acids (FPA) were determined through alkaline hydrolysis, wherein ferulic acid (86.22–90.49%) existed dominantly. Fujian "Cara Cara" showed the highest total phenolic index (TPI) and total flavonoid index (TFI) values, while the lowest TPI and TFI values were detect in Chongqing "Cara Cara". DPPH value showed positive correlation with TPC value ( r 2  = 0.921), while no correlation was found between ORAC and phenolic contents.